2014
DOI: 10.21856/j-pep.2014.3.03
|View full text |Cite
|
Sign up to set email alerts
|

To the Issue of the Abdominal Obesity Spread

Abstract: According to the results of measurement of height, weight and calculation of body mass index in 1059 inhabitants of a large industrial center (Kharkiv) over the age of 45 years, are actively traded in the policlinics, was characterized the frequency of abdominal obesity (criteria: waist and waist / hips ratio) with taking into account sex characteristics. It was found that 83 % of screening participants had an abdominal obesity, including 56 % — expressed abdominal obesity. Excessive accumulation of adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Abdominal type of obesity in combination with arterial hypertension, insulin resistance, disturbance of glucose tolerance, dyslipidemia and depression lead to a condition defined as a metabolic syndrome. It is reported that obesity and metabolic syndrome are found in women at this period 3 times more frequently than before menopause [3,6,9,10,20,21,28]. The deficiency of estrogen in the woman's body changes the distribution of adipose tissue from the peripheral type to the central one, reduces the tissues sensitivity to insulin [6,31].…”
Section: Analytical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal type of obesity in combination with arterial hypertension, insulin resistance, disturbance of glucose tolerance, dyslipidemia and depression lead to a condition defined as a metabolic syndrome. It is reported that obesity and metabolic syndrome are found in women at this period 3 times more frequently than before menopause [3,6,9,10,20,21,28]. The deficiency of estrogen in the woman's body changes the distribution of adipose tissue from the peripheral type to the central one, reduces the tissues sensitivity to insulin [6,31].…”
Section: Analytical Literature Reviewmentioning
confidence: 99%
“…Every year, the number of newly diagnosed cases of obesity among Ukrainians is steadily increasing. It should be noted that with age, the tendency to increase body weight is observed in both men and women, but women are more prone to obesity [4,6,7,8,9,10,15].…”
Section: Introductionmentioning
confidence: 99%